Decentralised international cooperation: insights from the Yogyakarta (Indonesia) - Gyeongsangbukdo (South Korea) partnership - Sri Issundari, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Developing decentralised international cooperation is not easy. Managing active and beneficial decentralised international cooperation amidst many inactive regional-international partnerships will be much more difficult. Geographical factors of distant regions, language differences, and lack of planning and coordination are often the leading causes of constrained and inactive regional international cooperation. This paper will map the factors that influence the success of the Yogyakarta (Indonesia)–Gyeongsangbukdo (South Korea) international collaboration so that it provides tangible and sustainable benefits. The paper is qualitative-analytical, which aims to explore the background of the success of regional-international cooperation amid the criticism of many inactive decentralised-international cooperation. Interviews with interviewees from BPPM (Women and Community Empowerment Agency) of Yogyakarta, the Directorate of Law and International Agreements at the Ministry of Foreign Affairs of the Republic of Indonesia, and YGSI (Global Saemaul Indonesia Foundation) provide the primary data sources. Secondary data sources are derived from reports, articles, and documents regarding Yogyakarta – Gyeongsangbukdo international cooperation. Based on research findings, two variables determine the success of Yogyakarta - Gyeongsangbukdo international cooperation: first, the two local governments’ readiness to carry out all stages of international collaboration, and second, active public participation in executing and managing activities.